Konsepsi Tangkisan Atau Bantahan Sebagai Hak Penerbit Surat Berharga (International Forum of Researchers and Lecturers, 2023)
In carrying out its obligations to issue marketable securities, sometimes there are some mistakes that are actually unintentional by the issuer, such as in writing the nominal amount, date, etc. where the issuer realizes that his mistakes after the issuance of the marketable securities can certainly harm the issuer, then the issuer can make rebuttal. This study aims to find out how the role of countermeasures or countermeasures in protecting mistakes made by marketable securities. Based on the research results, it is known that countermeasures or rebuttal can be a special right of the issuer of marketable securities because it can protect the issuer of securities from not paying for the marketable securities issued.